An umbrella review for preoperative rehabilitation in primary total knee arthroplasty: quality assessment and summary of evidence - Yan Zhao; Chong Tian; Songxin Tian; Wei Han; Hui Shi; Mingyu Cao; Jie Liu (BMC Musculoskeletal Disorders)
Abstract To evaluate the effects of preoperative rehabilitation in primary total knee arthroplasty patients and create an umbrella review. Web of science, PubMed, Epistemonikos, and Cochrane Library were searched from inception to 30 September 2023. This study combined the terms of total knee arthroplasty, and preoperative rehabilitation to retrieval relative systematic reviews (SR) and meta-analyses (MA). The 2 reviewers independently completed article screening, data extraction, and measure of methodological rigor quality. A Measurement Tool to Assess Systematic Reviews (AMSTAR-2) was used to measure the methodological quality of the included SRs. A total of 14 eligible SR and MA were eventually included in the qualitative analyses. The AMSTAR-2 indicated that the quality evaluation grade of 9 articles was ‘Critically low’ and the rest were ‘Low’. The findings indicate that exercise and physiotherapy, which are the primary preoperative rehabilitation measures, exhibit a negligible impact on postoperative pain and functional enhancement. Two studies of Meta-analyses combined with RCTs provided strong evidence that preoperative rehabilitation significantly reduces hospital length of stay by pooling data from multiple RCTs, and the results were statistically significant. Two other systematic reviews that pooled the results of existing studies also supported that preoperative rehabilitation reduces hospital length of stay. Nevertheless, the preponderance of studies proved inadequate in substantiating enhanced functional prognoses with preoperative rehabilitation. There was considerable heterogeneity in the selection of interventions and outcome metrics across the studies. Future research needs to address these issues through appropriate doses and fully described interventions.